Features of psychology-physiology factors, providing efficiency of technical-tactical actions of young tennis players 6–8 years - Лобода [V. Loboda], В'ячеслав Сергійович (Slobozhanskyi Herald of Science and Sport, 2013)
In the article there are the considered features of psychology-physiology factors which provide efficiency of technical-tactical actions of young tennis players 6–8 years. For young tennis players a technical level is not only subzero but also not stable, that compels sportsmen to be constantly distracted on the rightness of implementation of technical receptions, brakes speed, and often and rightness of choice of tactical decision. The cross-correlation analysis of technical-tactical actions and psychology-physiology indexes of young tennis players is conducted 6–8 years, on the basis of which it is possible to assume that these years of preparation of young tennis players are base, as there is an increase of amount of meaningful psychology-physiology internals and properties which substantially influence on efficiency of contention activity of young tennis players. The got results testify to the gradual increase of cross-correlation connections with age of sportsmen, especially in the indexes of playing a wall in age 8 years.